Determination of Yield and Botanical Composition of the Meadow and Grassland in Çolpan Village at the Shores of Lake Van - Mehmet Macit Ertuş (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out at the meadows and pastures in Çolpan village of Van province in 2020. In the study, matter yield, botanical composition, plant covered area, rate of decreaser/increaser/invader species were determined. The Loop method was used to determine the botanical composition. In grassland area were identified 69 species belonging to 17 families. In meadow area were identified 20 species belonging to 6 families. The amount of Poaceae, Fabaceae and other families found in the grassland area were determined as 18.66%, 15.65%, and 65.69%, respectively. In the meadow area, the amount of Poaceae, Fabaceae and other families were determined as 67.50%, 15.0%, and 17.50%, respectively. Artemisia spicigera (4.74%) Taeniatherum caput-medusae (5.0%) Arenaria serpyllifolia (5.0%) Medicago monantha (5.92%) species were the most common species found in the grassland area. Hordeum brevisubulatum (25.5%), Bromus scoparius (16.75%), and Taraxacum androssovii (9.25%) species were the most common species found in the meadow area. According to the ratio of good plants, pasture was classified as poor pasture and meadow was in the moderate meadow class. Grassland and meadow matter yields were found to be 91.4 kg/da and 385.2 kg/da, respectively. In the grassland of Çolpan village, invader species were found to be dense. It was concluded that grassland area should be improved.